If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-22=-8h+4h
We simplify the equation to the form, which is simple to understand
-22=-8h+4h
We move all terms containing h to the left and all other terms to the right.
+8h-4h=+22
We simplify left and right side of the equation.
+4h=+22
We divide both sides of the equation by 4 to get h.
h=5.5
| 2p-2(3-4p)=6(p-5)-12 | | 0.8=20 | | -3(2+5)=2(5t+7) | | 8(x+5)=60 | | 9b-8+6b=22 | | -(6x-11)+x-4= | | 2(x-4)=3x+8 | | -3y^2+16y-5=0 | | y^2+7=8 | | (-9+2i)-(2+9i)= | | 2l+2w-3=36 | | 10y=13+16x | | 26=2(x+3)+2(2x-6) | | 8c+7c=-27 | | 2x^2-6x-7=-x+4 | | h-81=9 | | 3+7x-(2+9x)= | | 8m+8-2m= | | 18+2x+x= | | 2x+20=50 | | 3x-4=16y | | 8y-xy=64 | | -2(5r+8)=-26 | | 7b+8b+4a+5a= | | x-2=4x+10 | | -13a=-1 | | 5-3x-3x=41 | | |2x+5|-=-2 | | 0=4v^2+19v+21 | | 4h+7=7h-8 | | 17b+2c+b-c= | | 6x+19x=-3(2x+8) |